Economic Burden of HIV in a Commercially Insured Population in the United States - Cindy Y. Chen; Prina Donga; Alicia K. Campbell; Babafemi Taiwo (Journal of Health Economics and Outcomes Research)
**Background:** With advances in antiretroviral therapy (ART), people with HIV infection are living longer. Pre-exposure prophylaxis (PrEP) to reduce HIV infection risk continues to be underutilized in high-risk individuals. Recent data on economic burden for patients with newly diagnosed HIV-1 or initiated with PrEP are limited.